STRATEGY FOR DEVELOPMENT OF LAYING QUAIL FARMING IN THE MANUNGGAL LIVESTOCK GROUP BINANGUN DISTRICT BLITAR REGENCY: socio-economic farming - Andaruisworo, Sapta; Nur Solikin; Erna Yuniati; Ardina Tanjungsari; Anifiatiningrum; Dino Fadilah Fanani; Siti Nailil Ngazizah (UNIVERSITAS ISLAM LAMONGAN, 2024)
This research is motivated by livestock development which is carried out to increase livestock production and productivity, as well as provide economic and social benefits to local communities. The livestock industry plays an important role in providing food and nutrition, especially in meeting the population's need for animal protein. The aim of this research is to find out what internal and external factors influence the development of egg-laying quail businesses in Tawangrejo Village, Binangun District, Blitar Regency and appropriate development strategies for egg-laying quail businesses in Tawangrejo Village, Binangun District, Blitar Regency. This research was conducted in the Manunggal quail livestock group in Tawangrejo Village, Binangun District, Blitar Regency. The method used is distributing questionnaires to obtain information and conducting observations and interviews to carry out further analysis related to business feasibility analysis and appropriate development strategies to be carried out. The conclusion of the results of this research is that the Manunggal quail livestock group breeder's business can be informed by each breeder while running the business that the business is worth running because it gets an R/C Ratio value of more than 1 and a B/C Ratio of more than 0, apart from that for every farm that is part of the group. The Manunggal quail livestock group obtains a break-even point value at different price BEP and unit BEP because it is influenced by the number of different fixed costs and variable costs and the number of livestock being reared. And based on the IFE and EFE matrix calculations in the Manunggal quail livestock group, the IFE matrix score was 3.14 and the EFE matrix was 3.22. Recommended; Based on the SWOT analysis of the Manunggal quail farming group, several strategies were found, namely improving the quality of quail egg products with a good grade, maintaining and continuing to improve infrastructure, facilities and infrastructure for business development, monitoring and continuing to improve the system in laying quail farms to meet the need for quail eggs. in society.